A Picture Book of Amelia Earhart - Adler, David A.; Nang Chan Yeema (New York, USA Scholastic Inc., 1986)
Amelia Earhart was America's "First Lady of the Air." She was a courageous flyer, a pioneer. She risked her life to prove that in the air, and elsewhere, women were up to the challenge. She certainly was.
Keywords: Biography